The prevalence of tuberculosis among Iranian elderly patients admitted to the infectious ward of hospital: A systematic review and meta-analysis. (December 2016) - Azami, M.; Sayehmiri, K.; YektaKooshali, M.H.; HafeziAhmadi, M.R.
Abstract: Aims and objectives: Age increasing is caused physiological changes in the human body, such as reducing the power of the immune system. Weakened immune systems are more susceptible to bacterial infections like tuberculosis. So, this present study was performed for evaluating the prevalence of tuberculosis among Iranian elderly patients admitted to the infectious ward of a hospital. Methods: This systematic review and meta-analysis study has been done based on PRISMA guidelines. A comprehensive search was conducted in Iranian and International databases included: Magiran, Iranmedex, IranDoc, SID, Medlib, Scopus, PubMed, Science Direct, Cochrane, Web of Science, Springer, Wiley Online Library as well as the Google Scholar search engine in the period 1990–2016 by two independent researchers using the Mesh keywords. All of the reviewed studies that had inclusion criterion were been evaluated. The diagnosis of tuberculosis were considered results of physical examination, PPD (Purified Protein Derivative) test, Blood tests, Imaging tests and sputum test. The data were analyzed by using random effects model with the software Stata-Ver.11.1. Results: Five studies with a total number of 2, 956 elderly patients were included. The prevalence of tuberculosis among Iranian elderly patients admitted to the infectious ward of the hospital was estimated to be 15% (95%CI: 1–30). The relationship between prevalence of tuberculosis with a year of study was not statistically significant ( P =0.371). Conclusion: This will be the first systematic review of tuberculosis prevalence among elderly patients admitted to the infectious ward in Iran. This study showed a high prevalence of Tuberculosis and it is recommended considering tuberculosis as a differential diagnosis in elderly patients with infectious symptoms.